2016
DOI: 10.1021/jacs.6b08211
|View full text |Cite
|
Sign up to set email alerts
|

Why is the Ir(III)-Mediated Amido Transfer Much Faster Than the Rh(III)-Mediated Reaction? A Combined Experimental and Computational Study

Abstract: The mechanism of the Ir(III) and Rh(III)-mediated C-N coupling reaction, which is the key step of catalytic C-H amidation, was investigated in an integrated experimental and computational study. Novel amidating agents containing a 1,4,2-dioxazole moiety allowed for designing a stoichiometric version of the catalytic C-N coupling reaction and giving access to reaction intermediates that reveal details about each step of the reaction. Both DFT and kinetic studies strongly point to a mechanism where the M(III) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 135 publications
2
77
0
2
Order By: Relevance
“…Detailed explanations will be given in the DFT calculation section. [86][87][88][89][90][91][92][93][94] and predictive studies. [95][96][97][98][99][100][101][102][103][104] To gain a better understanding of the polymerization processes discussed above, detailed theoretical studies were essential.…”
Section: Almentioning
confidence: 99%
“…Detailed explanations will be given in the DFT calculation section. [86][87][88][89][90][91][92][93][94] and predictive studies. [95][96][97][98][99][100][101][102][103][104] To gain a better understanding of the polymerization processes discussed above, detailed theoretical studies were essential.…”
Section: Almentioning
confidence: 99%
“…[40] Metalation of 2-phenylpyridine throughC ÀHa ctivation generated rhodacycle I (M = Rh),w hich could coordinate to the 2-phenylpyridine substrate to afford an off-cyclic species( II). [40] Metalation of 2-phenylpyridine throughC ÀHa ctivation generated rhodacycle I (M = Rh),w hich could coordinate to the 2-phenylpyridine substrate to afford an off-cyclic species( II).…”
Section: Cànformation With Dioxazolonesmentioning
confidence: 99%
“…Subsequently,d etailed experimental and computational studies on the CÀNc oupling reactions with Rh III and Ir III were reported( Scheme 30 a). [40] Metalation of 2-phenylpyridine throughC ÀHa ctivation generated rhodacycle I (M = Rh),w hich could coordinate to the 2-phenylpyridine substrate to afford an off-cyclic species( II). Reversible ligand exchange with an aminatinga gent,f ollowed by CÀNi nsertioni nto the RhÀC bond with the extrusion of CO 2 ,w ould lead to another rhodacyclic species(IV).…”
Section: Cànformation With Dioxazolonesmentioning
confidence: 99%
“…[5] In komplementärer Weise berichteten Blakey et al über die allylische Aminierung von b-substituierten Styrolen unter Verwendung von Cp*Rh III als Katalysator (Schema 1A (ii)). [8,9] Aufgrund unserer Erfahrung mit Cp*Rh III -katalysierten allylischen C-H-Funktionalisierungen haben wir angenommen, dass ein Rh III -Allyl-Intermediat ambiphile Eigenschaften haben kçnnte. [7] Chang et al führten Dioxazolone als stabile Nitrenvorläufer fürdie redoxneutrale ortho-dirigierte C-H-Amidierung von Arenen ein, wobei Curtius-artige Umlagerungen vermieden werden konnten, die in der Metallnitren-Chemie als problematisch gelten.…”
unclassified
“…[7] Chang et al führten Dioxazolone als stabile Nitrenvorläufer fürdie redoxneutrale ortho-dirigierte C-H-Amidierung von Arenen ein, wobei Curtius-artige Umlagerungen vermieden werden konnten, die in der Metallnitren-Chemie als problematisch gelten. [8,9] Aufgrund unserer Erfahrung mit Cp*Rh III -katalysierten allylischen C-H-Funktionalisierungen haben wir angenommen, dass ein Rh III -Allyl-Intermediat ambiphile Eigenschaften haben kçnnte. [10] Während in mehreren Berichten die elektrophile Natur von Cp*Rh III -Allyl-Intermediaten beschrieben wird, die durch nukleophile Kupplungsreagenzien abgefangen werden kçnnen, wurde die Reaktion der Rh-Allyl-Einheit mit einem Elektrophil noch nicht beschrieben.…”
unclassified